2016
DOI: 10.1128/iai.00735-16
|View full text |Cite
|
Sign up to set email alerts
|

The Phosphotransfer Protein CD1492 Represses Sporulation Initiation in Clostridium difficile

Abstract: The formation of spores is critical for the survival of Clostridium difficile outside the host gastrointestinal tract. Persistence of C. difficile spores greatly contributes to the spread of C. difficile infection (CDI), and the resistance of spores to antimicrobials facilitates the relapse of infection. Despite the importance of sporulation to C. difficile pathogenesis, the molecular mechanisms controlling spore formation are not well understood. The initiation of sporulation is known to be regulated through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
57
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 70 publications
2
57
1
Order By: Relevance
“…Interestingly, CD1492 , encoding a kinase sharing 30% identity with Cac0437, was down‐regulated in the sigB mutant. Furthermore, it was recently reported that CD1492 negatively controls sporulation (Childress et al ., ). In conclusion, we propose that σ B controls sporulation initiation by modulating the level of phosphorylation of Spo0A as suggested in B. subtilis .…”
Section: Resultsmentioning
confidence: 97%
“…Interestingly, CD1492 , encoding a kinase sharing 30% identity with Cac0437, was down‐regulated in the sigB mutant. Furthermore, it was recently reported that CD1492 negatively controls sporulation (Childress et al ., ). In conclusion, we propose that σ B controls sporulation initiation by modulating the level of phosphorylation of Spo0A as suggested in B. subtilis .…”
Section: Resultsmentioning
confidence: 97%
“…AM180355). CLC Genomics Workbench v9.0 was used for all variant analysis, as previously described (Childress et al, 2016). No nucleotide changes were observed between the mutant and parent strain genomes.…”
Section: Cloning and Strain Constructionmentioning
confidence: 99%
“…C. difficile cultures were grown in BHIS medium supplemented with 0.1% taurocholate and 0.2% fructose until mid-exponential phase (i.e., OD 600 of 0.5), and 0.25 ml aliquots were plated onto 70:30 agar supplemented with 2 µg/ml thiamphenicol (79). After 24 h growth, ethanol resistance assays were performed as previously described (84, 85). Briefly, the cells were removed from plates after 24 h (H 24 ) and suspended in BHIS medium to an OD 600 of ∼1.0.…”
Section: Methodsmentioning
confidence: 99%